Galangin and Pinocembrin from Propolis Ameliorate Insulin Resistance in HepG2 Cells via Regulating Akt/mTOR Signaling. (21st October 2018) - Liu, Yinkang; Liang, Xiali; Zhang, Gensheng; Kong, Lingjie; Peng, Wenjun; Zhang, Hongcheng
Abstract : Insulin resistance has a critical role in type 2 diabetes. The aim of this study was to investigate the effect of pinobanksin, galangin, chrysin, and pinocembrin from propolis on insulin resistance. Our study shows that galangin and pinocembrin can ameliorate insulin resistance; on the contrary, pinobanksin and chrysin are ineffective. Galangin and pinocembrin treatments substantially increase glucose consumption and glycogen content by enhancing the activities of hexokinase and pyruvate kinase. Galangin treatment with 80 μ M increased hexokinase and pyruvate kinase activities by 21.94% and 29.12%, respectively. Moreover, we hypothesize that galangin and pinocembrin may have a synergistic effect on the improvement of insulin resistance via Akt/mTOR signaling pathway, through distinctly upregulating the phosphorylation of IR, Akt, and GSK3 β and remarkably downregulating the phosphorylation of IRS. Most notably, this is the first study to our knowledge to investigate pinocembrin about the alleviation of insulin resistance. Our results provide compelling evidence for the depth development of propolis products to ameliorate insulin resistance.